2016
DOI: 10.1108/ijpsm-02-2016-0029
|View full text |Cite
|
Sign up to set email alerts
|

Contracting out parks and roads maintenance in England

Abstract: Purpose Different models have been adopted in England over time to organize public service delivery. This paper explores contracting-out, a prevalent model of public service delivery in England, in relation to parks and roads maintenance delivery by examining private contractors' performance according to local authority stakeholders. Design/methodology/approach Since the Conservative government was in power during the 1980s, local authorities have been an arena for experimentation of contracting-out to private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…However, the difference may be a result of differences in the type of maintenance services, as the Norwegian municipalities mostly used private contractors for provision of services they could not provide themselves. Dempsey et al (2016) found that satisfaction levels with private provision among English local authorities on the average were surprisingly high compared to the legacy of contracting out from the era of compulsory competitive tendering in the 1980s and 1990s.…”
Section: Service Outcomesmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the difference may be a result of differences in the type of maintenance services, as the Norwegian municipalities mostly used private contractors for provision of services they could not provide themselves. Dempsey et al (2016) found that satisfaction levels with private provision among English local authorities on the average were surprisingly high compared to the legacy of contracting out from the era of compulsory competitive tendering in the 1980s and 1990s.…”
Section: Service Outcomesmentioning
confidence: 96%
“…In particular, it can be argued that contracting out has been used as a means through which governments implement an objective of cost reduction (as well as objectives related to reducing the number of staff in public organizations). This is perhaps most evident in the policies on compulsory competitive tendering in the UK which provided a tight regulation of the use of contracting out as a clear cost-reducing mechanism (Dempsey et al, 2016). A special case, which also illuminates the importance of taking objectives into account, is the study of contracting out in Norwegian municipalities by Leiren et al (2016).…”
Section: Competitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coproduction has been overlooked in state-run systems (e.g., Italy and France) (Palumbo et al, 2016). That is in contrast to Nordic patient choice models (Bendz, 2017) or Anglo-Saxon consumer-driven market where responsibilities are increasingly shared between different combinations of public, private, third, and community sector stakeholders (Dempsey, Burton, & Selin, 2016). There are significant benefits to coproduction.…”
Section: Discussionmentioning
confidence: 95%
“…As a reaction to the problems that CCT exacerbated in terms of deskilling parks management and reducing many tasks to grounds maintenance [85], the New Labour government (elected in 1997) introduced the Best Value regime. While this focussed on the quality of management, it put inordinate pressure on local governments to put resources into evaluating and measuring parks quality for national scrutiny (the then-Audit Commission).…”
Section: Policymentioning
confidence: 99%